2012
DOI: 10.1002/zamm.201200018
|View full text |Cite
|
Sign up to set email alerts
|

Global weak solutions for coupled transport processes in concrete walls at high temperatures

Abstract: Key wordsInitial-boundary value problems for second-order parabolic systems, nonlinear boundary conditions, global existence of weak solutions, coupled heat and mass transport.We consider an initial-boundary value problem for a fully nonlinear coupled parabolic system with nonlinear boundary conditions modeling hygro-thermal behavior of concrete at high temperatures. We prove a global existence of a weak solution to this system on any physically relevant time interval. The main result is proved by an approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We refer to (8)-( 18) as (P ε ) -our reference microscopic model. Note that the Soret and Dufour coefficients determine the structure of the particular crossdiffusion system (see [12], [26] [2], [3], [22], [29]). The coefficients a i and b i describe the deposition interaction between u ε i and v ε i .…”
Section: Setting Of the Model Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We refer to (8)-( 18) as (P ε ) -our reference microscopic model. Note that the Soret and Dufour coefficients determine the structure of the particular crossdiffusion system (see [12], [26] [2], [3], [22], [29]). The coefficients a i and b i describe the deposition interaction between u ε i and v ε i .…”
Section: Setting Of the Model Equationsmentioning
confidence: 99%
“…Accounting for the interplay between heat, diffusion, attraction-repulsion, and deposition of the colloidal particles is of paramount importance for a number of applications including the dynamics of the colloidal suspension in natural or man-made products (e.g. milk, paints, toothpaste) [12], drug-delivery systems [2], hierarchical assembly of biological tissues [27], group formation in actively interacting populations [30], or heat stocks in porous materials [4]. Further details on colloids and their practical relevance are given in [10,23], e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Recently, in Amaziane et al, 42 the authors have shown the existence of weak solutions to the coupled heat transport and two-phase immiscible incompressible flows through porous materials. An existence analysis for problems with a specific structure modeling the heat and moisture transport in cementitious materials can be found in previous studies [43][44][45] (including the transport of dissolved chemical species, chemical reactions and hydration phenomena) and in Beneš, 46 where the author introduced the hygro-thermal model coupled with quasi-static evolution equations modeling elastic and inelastic mechanical deformations.…”
Section: A Brief Bibliographical Surveymentioning
confidence: 99%
“…Practical applications of such approach would investigate the problem of reducing a heterogeneous material to a homogeneous, specifically, predicting the response of refractory concrete to high-temperature exposure in steel furnaces. In nature, the impact of heat and mass transfer processes become particularly evident at high temperatures, where the increased pressure in pores, large temperature gradients, and temperature-induced creep may lead to catastrophic service failures [11]. Benes et al [12] discussed a nonlinear numerical scheme arising from the implicit time discretization of the Bazant-onguthai model (with crossdiffusion) for hygrothermal behavior of concrete at high temperatures.…”
Section: Introductionmentioning
confidence: 99%